Unlocking phenotypic plasticity provides novel insights for immunity and personalized therapy in lung adenocarcinoma - Wang, Feng; Du, Hongjuan; Li, Bibo; Luo, Zhibin; Zhu, Lei (Frontiers in Genetics, 2022)
Background: Unlocking phenotype plasticity (UPP) has been shown to have an essential role in the mechanism of tumor development and therapeutic response. However, the clinical significance of unlocking phenotypic plasticity in patients with lung adenocarcinoma is unclear. This study aimed to explore the roles of unlocking phenotypic plasticity in immune status, prognosis and treatment in patients with lung adenocarcinoma (LUAD). Methods: Differential expressed genes (DEGs) and clinical information of UPP were selected from the cancer genome atlas (TCGA) database, and the GO, KEGG enrichment analyses were performed. The independent prognostic genes were determined by univariate and multivariate Cox regression, and the UPP signature score was constructed. Patients with LUAD were divided into high- and low-risk groups according to the median of score, and the immunocytes and immune function, the gene mutation, drug sensitivities between the two groups were analyzed. Finally, the results were validated in the GEO database. Results: Thirty-nine significantly differentially expressed genes were determined. Enrichment analysis showed that UPP-related genes were related to protein polysaccharides and drug resistance. The prognostic results showed that the survival of patients in high-risk group was poorer than that in the low-risk group (P<0.001). In the high- and low-risk groups, single nucleotide polymorphism (SNP) and C>T are the most common dissent mutations. The contents of immune cells were significantly different between high- and low-risk groups. And the immune functions were also significantly different, indicating that UPP affects the immunity in LUAD. The results from TCGA were validated in the GEO. Conclusion: Our research has proposed a new and reliable prognosis indicator to predict the overall survival. Evaluation of the UPP could help clinician to predict therapeutic responses and make individualized treatment plans in patients with LUAD.